India and ‘Indo-Pacific’: Involvement rather than Entanglement - Raghavendra Mishra
While the Pacific pole of the Indo-Pacific is important, the primacy of the Indian Ocean in the national strategic calculus is far more critical due to energy dependency on the Middle East, increasing economic linkages with Africa, and the security of major sea lines of communication passing through the western Indian Ocean. The Indian strategic policy framework should factor the nuances of emerging multi-polarity, and a deepening of ‘vertical and horizontal intermeshing’ brought about by the globalisation process. While the stance of ‘strategic autonomy’ remains inviolate, the tenets of maintaining equidistance and balance among the power centres may prove to be a constraint. The simultaneous management of mutually opposing paradigms across the strategic threads of politics–diplomacy– economics–security could be best served by a ‘functional transactional approach’ instead of a rigid straight-line, single point of departure policy.